RETRACTED: Influence of cultivation techniques on productivity and quality of meadow clover - Mazin Aleksey; Spiridonov Anatoly; Arzhanov Georgy (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001